Reference quality genome sequence of Indian pomegranate cv. `Bhagawa' (Punica granatum L.) - Roopa Sowjanya, P.; Shilpa, Parashuram; Patil, Goudappa Prakash; Babu, Dhinesh Karuppannan; Sharma, Jyotsana; Sangnure, Vipul R.; Mundewadikar, Dhananjay M.; Natarajan, Purushothaman; Marathe, Arvind Rajiv; Reddy, Umesh K.; Singh, Vikram Nripendra (Frontiers in Plant Science, 2022)
Pomegranate is an important fruit crop for ensuring livelihood and nutrition security in fragile semi-arid regions of the globe having limited irrigation resources. This is a high-value, nutritionally rich, and export-oriented agri-commodity that ensures high returns on investment to growers across the world. Although it is a valuable fruit crop, it has received only a limited genomics research outcome. To fast-track the pomegranate improvement program, de novo whole-genome sequencing of the main Indian cultivar `Bhagawa' was initiated by the Indian Council of Agricultural Research-National Research Center on Pomegranate (ICAR-NRCP). We have demonstrated that a combination of commercially available technologies from Illumina, PacBio, 10X Genomics, and BioNano Genomics could be used efficiently for sequencing and reference-grade de novo assembly of the pomegranate genome. The research led to a final reference-quality genome assembly for `Bhagawa' of 346.08 Mb in 342 scaffolds and an average N50 of 16.12 Mb and N90 of 1088.62 Kb. This assembly covered more than 98% of the estimated pomegranate genome size, 352.54 Mb. The LTR assembly index (LAI) value of 10 and 93.68% Benchmarking Universal Single-Copy Orthologs (BUSCO) completeness score over the 1,440 ortholog genes of the completed pomegranate genome indicates the quality of the assembled pomegranate genome. Furthermore, 29,435 gene models were discovered with a mean transcript length of 2,954 bp and a mean coding sequence length 1,090 bp. Four transcript data samples of pomegranate tissues were mapped over the assembled `Bhagawa' genome up to 95% significant matches, indicating the high quality of the assembled genome. We have compared the `Bhagawa' genome with the genomes of the pomegranate cultivars `Dabenzi' and `Taishanhong.' We have also performed whole-genome phylogenetic analysis using Computational Analysis of Gene Family Evolution (CAFE) and found that Eucalyptus grandis and pomegranate diverged 64 (60-70) million years ago. About 1,573 protein-coding resistance genes identified in the `Bhagawa' genome were classified into 32 domains. In all, 314 copies of miRNA belonging to 26 different families were identified in the `Bhagawa' genome. The reference-quality genome assembly of `Bhagawa' is certainly a significant genomic resource for accelerated pomegranate improvement.
Keywords: genome sequencing; hybrid genome assembly; Long Terminal Repeats Assembly Index (LAI); PacBio; pomegranate